475 Co-designing an intervention to support safe medicines self-management for older people living with frailty and polypharmacy. (13th April 2023) - Previdoli, G; Silcock, J; Alldred, D; Cheong, V-L; Tyndale-Briscoe, S; Okeowo, D; Fylan, B
Abstract: Introduction: Older people face numerous challenges and safety risks when managing multiple medicines. They are required to cope with complex and changing regimens and co-ordinate input from multiple healthcare professionals. If not well managed, medicines can cause harm, and older people are more susceptible to errors. Some older people can devise and implement strategies to manage their medicines, e.g. creating checklists, ensuring timely supplies, solving problems, and seeking help (1). However, no interventions address the multiple tasks polypharmacy patients must perform to safely manage their regimens. Aim: To develop an intervention to support medicines self-management for older people living with frailty and polypharmacy using experience-based co-design (EBCD) (2). Methods: Following video or audio-recorded qualitative interviews with 32 older people taking 5 or more medicines, a 'trigger film' of patients' medicines management experiences was produced and used during EBCD to facilitate priority setting. Separate meetings were held (1) with 16 staff (2 GPs, 4 GP practice administrators, 4 GP practice pharmacists, 1 practice lead, 2 senior nurses, 2 pharmacy technicians, 1 community pharmacist) and (2) with 13 patients and 2 family members, followed by a joint meeting with 8 older people and 9 staff where a shared set of three priorities was agreed. Two subsequent co-design workshops with 6 patients, 2 family members and 7 staff developed three candidate interventions. Workshop 1 explored key themes from the trigger film to develop solutions. Workshop 2 reviewed solutions and further developed design ideas. Intervention components were merged and those addressing patient safety challenges were retained to form the prototype intervention. Ethical approval was obtained for the interviews included in the trigger film, but not required for EBCD. EBCD meetings and workshops were conducted as quality improvement: people involved were collaborators, personal information was not captured, discussions were not recorded or analysed. Results: Co-design priorities were to support patients in: day-to-day practical medicines management; understanding the wider medicines management system; communication with healthcare teams. The three solutions were: a quick-start guide to managing multiple medicines including talking about medicines and managing new routines; tips and tricks to support day-to-day management, including planning and adherence tools; a tool supporting preparation for medication reviews and asking questions about medicines. After merging intervention components and identifying those addressing medicines-self-management patient safety challenges, five areas were retained for the prototype intervention: checking what you get; keeping on top of supplies; monitoring how you take your medicines; times when problems are more likely; and how do I know if I need help? Discussion/Conclusion: Through EBCD patients and staff worked together to improve people's experiences of managing medicines and to enhance safety. The prototype intervention addresses five areas where older people with complex medicines regimens require support. The intervention requires feasibility testing and subsequent robust evaluation. Strengths and limitations: A variety of staff roles joined the co-design, offering multiple different perspectives on medicines management EBCD meetings and workshops were run online to avoid Covid infections. This may have excluded older people with no access to internet. References: 1. Tomlinson J, Silcock J, Smith H, Karban K, Fylan B. Post-discharge medicines management: the experiences, perceptions and roles of older people and their family carers. Health Expect [Internet]. 2020;23(6):1603–13. Available from: http://dx.doi.org/10.1111/hex.13145 2. Fylan B, Tomlinson J, Raynor DK, Silcock J. Using experience-based co-design with patients, carers and healthcare professionals to develop theory-based interventions for safer medicines use. Res Social Adm Pharm [Internet]. 2021;17(12):2127–35. Available from: http://dx.doi.org/10.1016/j.sapharm.2021.06.004